From plate to plough: Sowing nutrition security - Bouis, Howarth E.; Gulati, Ashok (Indian Express Group, 2020)
On the occasion of World Food Day (October 16), prime minister Narendra Modi issued a commemorative coin of Rs 75 and dedicated 17 bio-fortified varieties of eight crops to the nation to celebrate the establishment of Food and Agriculture Organisation (FAO) 75 years ago in 1945.